Integrated Lean-BPM Model to Increase Order Fulfillment in MYPES in the Textile Sector - Marquez Ordinola, Alithu Ankara (2022)
The textile industry is one of the most important developments of the Peruvian economy; However, this sector has been presenting a series of challenges such as the necessity of reduce some relevant costs, high percentages of waste and low efficiency in the production line, all this problems evidence a low availability of machines that ranges from the hand with a disorganized production. In this way, the problematics mentioned before, generates cycle times shorter than Takt times, bringing as a fundamental consequence, the non-fulfillment of planned orders. In this research, we proposed an integrated model that uses lean manufacturing tools such as standardized work, SMED and TPM, hand in hand with the BPM philosophy, which provides a process-oriented approach. In this way, the proposed model seeks to increase the current order fulfillment indicator of 72%, which, after implementation, showed an increase of 12.4%, verifying the effectiveness of the proposed model, in which the results were corroborated through a simulation.